A Preliminary Study of Livelihood Challenges in Water Settlement Area in Northern Sarawak, Malaysia - Shyafiena, Abd Aziz; Farah, Zaini (Human Resource Management Academic Research Society, 2023)
Water settlement area, also known as water village, is situated above the water and is frequently referred to as a fishing village due to the majority of the population's occupation as fishermen. It consists of a cluster of typical river-long stilt settlements, most of which are located near or outside the city. This paper is a preliminary study in identifying the difficulties of sustaining a living in a water settlement area. The significance of this paper lies in its examination of the obstacles related to the safety of villagers on the water. In this article, qualitative face-to-face interviews with respondents served as the research method, and the obtained data were analysed using thematic analysis. There are three identified challenges that can affect community safety in this geographical area. Water village communities are among the most vulnerable populations, more likely than others to require humanitarian aid or be excluded from financial and social services. Consequently, this article can also be used as a relevant resource for the development and improvement of strategies related to the same problem that occurs in other villages on water and can increase the level of safety for villagers.